Positive electrode material and preparation method thereof, and battery

By using lithium nickel-cobaltate composite oxides and optimized sintering treatment technology in the positive electrode material, the separation degree and particle structure of its crystal surface characteristic peaks are solved, and the problems of polarization and side reactions of the positive electrode material during charging and discharging are solved. Achieve better cycle stability and rate performance.

CN117747776BActive Publication Date: 2025-02-18BTR (JIANGSU) NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311706975.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2025-02-18
Estimated Expiration
2043-12-13

AI Technical Summary

Technical Problem

During the charging and discharging process of existing positive electrode materials, there is a significant increase in the diffusion path of lithium ion, serious electrochemical and concentration polarization, and the intensification of side reaction between the material and the electrolyte, resulting in a decrease in cycle life and safety performance.

Method used

The lithium nickel-cobaltate composite oxide is used as the positive electrode material, and the peaks of the (104) crystal surface characteristic peaks are measured by XRD, and the resolution of the two diffraction peaks is controlled within the range of 0.7 to 2.0, combined with multi-step temperature-raising sintering treatment and the use of coating agents to optimize the particle strength and internal defect structure of the cathode material.

Benefits of technology

Improve the particle strength of the cathode material, reduce polarization phenomenon, improve cycle stability and rate performance, so that the cathode material has both excellent energy density and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117747776B_ABST
    Figure CN117747776B_ABST
Patent Text Reader

Abstract

The present application relates to a positive electrode material and a preparation method thereof, and a battery. The positive electrode material is a nickel cobalt lithium composite oxide. The positive electrode material is measured by XRD to obtain a characteristic peak I(104) corresponding to the (104) crystal plane of the positive electrode material. The characteristic peak I(104) is separated to obtain two diffraction peaks. The separation degree α of the two diffraction peaks satisfies: 0.7≤α≤2.0. The technical solution provided by the present application can improve the particle strength of the positive electrode material and reduce the polarization phenomenon of the positive electrode material, so that the positive electrode material has both excellent cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a positive electrode material and a preparation method thereof, and a battery. Background Art

[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their high energy density, good safety performance, long cycle life and environmental friendliness. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). Therefore, researchers currently focus on developing large-capacity and high-voltage positive electrode materials to improve the energy density of lithium-ion batteries.

[0003] The commonly used layered ternary positive electrode materials show the characteristics of high capacity, high voltage, good cycle life and good safety, and have become the main positive electrode materials for the development of power batteries. However, with the increase of nickel content in ternary positive electrode materials, it is inevitable that problems such as lithium-nickel mixing, structural degradation, and reduced thermal stability will occur. Existing positive electrode materials have fewer internal defects. When the particle size is large, the diffusion path of lithium ions increases significantly during charging and discharging, resulting in serious electrochemical and concentration polarization phenomena, and the electrical performance of the battery is affected. In addition, the increase in nickel content intensifies the degree of side reactions between the material and the electrolyte. As the degree of charging and discharging deepens, the expansion / contraction degree and internal stress of the positive electrode material grains intensify, the positive electrode material particles are prone to cracking and pulverization, and the battery cycle life and safety performance are affected.

[0004] Therefore, how to simultaneously improve the particle strength of the positive electrode material and reduce the polarization phenomenon of the positive electrode material so that the positive electrode material has both better cycle stability and rate performance is still a technical problem that needs to be solved. Summary of the invention

[0005] The purpose of the present application is to provide a positive electrode material and a preparation method thereof, and a battery, which can improve the particle strength of the positive electrode material and reduce the polarization phenomenon of the positive electrode material, so that the positive electrode material has both excellent cycle stability and rate performance.

[0006] In a first aspect, the present application provides a positive electrode material, wherein the positive electrode material is a nickel-cobalt-lithium oxide composite oxide;

[0007] The positive electrode material is measured by XRD to obtain a characteristic peak I(104) corresponding to the (104) crystal plane of the positive electrode material. The characteristic peak I(104) is separated into two diffraction peaks, and the separation degree α of the two diffraction peaks satisfies: 0.7≤α≤2.0.

[0008] In some embodiments, the positive electrode material satisfies the following relationship (1): 1≤T-(1.04α-0.25α2 +0.004*D 50 2 -0.02*D 50 )≤1.5, where T represents the tap density of the positive electrode material in g / cm 3 ;D 50 It represents the median particle size of the positive electrode material in μm.

[0009] In some embodiments, the positive electrode material satisfies the following relationship (2): 125≤C-(100*n Ni -D 50 *α 2 )≤135; where C represents the gram capacity of the positive electrode material, in mAh / g; D 50 Indicates the median particle size of the positive electrode material, in μm; n Ni It represents the molar ratio of Ni element in all metal elements except Li element in the positive electrode material.

[0010] In some embodiments, the positive electrode material satisfies the following relationship (3): 1800≤L-(2245α-5000*n Ni +100*D 50 )≤2400; where L represents the cycle life of the positive electrode material; D 50 Indicates the median particle size of the positive electrode material, in μm; n Ni It represents the molar ratio of Ni element in all metal elements except Li element in the positive electrode material.

[0011] In some embodiments, the tap density of the cathode material is T g / cm 3 , 1.7≤T≤2.5.

[0012] In some embodiments, the median particle size of the positive electrode material is D 50 μm, 3≤D 50 ≤16.

[0013] In some embodiments, the gram capacity of the positive electrode material is C mAh / g, 140≤C≤230.

[0014] In some embodiments, in the positive electrode material, 0.33≤n Ni ≤1.

[0015] In some embodiments, the cycle life of the positive electrode material is L cycles, 300≤L≤6000.

[0016] In some embodiments, the cathode material is a single crystal cathode material.

[0017] In some embodiments, the chemical formula of the positive electrode material is Li a Ni x Co y M1 z M2 k O2, wherein M1 is selected from Mn and / or Al, and M2 includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La and Dy; wherein 0.9<a≤1.1, 0.33≤x≤1, 0≤y≤0.33, 0<z<0.33, 0≤k<0.1, and x+y+z+k=1.

[0018] In a second aspect, the present application provides a method for preparing a positive electrode material, the method comprising the following steps:

[0019] A mixture containing a positive electrode material precursor and a lithium source is subjected to a primary sintering treatment, and the primary sintering product is crushed to obtain a positive electrode material; wherein the primary sintering treatment includes N step-by-step temperature rising sections and a constant temperature section performed in sequence, N ≥ 3;

[0020] Each step heating section includes n sub-stages with different heating rates, n≥2, the heating rate of the nth sub-stage is greater than the heating rate of the first sub-stage, and the heating rate of the nth sub-stage is a non-negative value.

[0021] In some embodiments, the chemical formula of the cathode material precursor is Ni a1 Co b1 M1 c1 O d , wherein 0.33≤a1≤1, 0≤b1≤0.33, 0≤c1<0.33, 4 / 3≤d≤3 / 2, and a1+b1+c1=1, and M1 is selected from Mn and / or Al.

[0022] In some embodiments, the chemical formula of the cathode material precursor is Ni a2 Co b2 M1 c2 (OH)2, wherein 0.33≤a2≤1, 0≤b2≤0.33, 0≤c2<0.33, and a2+b2+c2=1, and M1 is selected from Mn and / or Al.

[0023] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, lithium acetate, lithium sulfate, and lithium oxalate.

[0024] In some embodiments, the added amounts of the lithium source and the cathode material precursor satisfy the following conditions: the ratio of the molar amount of Li to the total molar amount of all metals in the cathode material precursor is (0.9-1.1):1.

[0025] In some embodiments, the mixture further comprises a dopant comprising a metal M2, wherein the M2 metal comprises at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La, and Dy.

[0026] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 20%.

[0027] In some embodiments, the maximum temperature of the step-temperature rising section is 700°C to 1000°C.

[0028] In some embodiments, the time of the step-temperature increase section is 6 hours to 14 hours.

[0029] In some embodiments, the sintering temperature of the constant temperature section ranges from (1150-500*n Ni )℃~(1150-280*n Ni )℃,n Ni It represents the molar ratio of Ni element in all metal elements except Li element in the positive electrode material.

[0030] In some embodiments, the constant temperature section includes alternating temperature-lowering subsections and temperature-raising subsections, and the temperature of the temperature-lowering subsection in the constant temperature section is lower than the temperature of the adjacent temperature-raising subsection.

[0031] In some embodiments, the amount of the dopant added is controlled so that the ratio of the molar amount of M2 to the total molar amount of the transition metal in the prepared positive electrode material is (0-0.1):1.

[0032] In some embodiments, the method further comprises: mixing the primary sintering product with a coating agent containing metal M2, and then performing a secondary sintering process to obtain a positive electrode material.

[0033] In some embodiments, the metal M2-containing coating agent, the M2 metal includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La and Dy.

[0034] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 20%.

[0035] In some embodiments, the secondary sintering process is performed at a temperature of 300°C to 900°C.

[0036] In some embodiments, the holding time of the secondary sintering treatment is 6 hours to 24 hours.

[0037] In some embodiments, the mass ratio of the coating agent containing the metal M2 to the primary sintering product is (0-0.1):1.

[0038] In a third aspect, the present application provides a battery, wherein the lithium-ion battery comprises the positive electrode material described in the first aspect.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The positive electrode material provided in the present application controls the two diffraction peaks obtained by the peak separation of the characteristic peak I (104) corresponding to the (104) crystal plane of the positive electrode material, and the separation of the two diffraction peaks is in the range of 0.7 to 2.0. On the one hand, it can ensure that the particle size of the positive electrode material is within a suitable range, and reduce the deterioration of the capacity and rate performance caused by the substantial increase in the diffusion distance of lithium ions caused by excessively large particles. In addition, the appropriate particle size can improve the structural strength of the particles, improve the cracking / powdering of particles under high rolling pressure and high voltage windows, and improve the cycle performance of the positive electrode material. On the other hand, the separation degree is in the range of 0.7 to 2.0, which can ensure that the degree of internal defects of the particles of the positive electrode material is within a suitable range, improve the problem of low Li ion diffusion rate caused by insufficient internal defects of the particles, and after the increase of internal defects of the particles, the diffusion path of lithium ions can be enriched, and the time required for lithium ion diffusion can be reduced, so that the degree of lithium deintercalation inside and on the surface of the positive electrode material particles tends to be consistent, and the polarization phenomenon between the surface and the inside of the particles is improved. Therefore, the positive electrode material provided in the present application can improve the particle strength of the positive electrode material and reduce the polarization phenomenon of the positive electrode material, so that the positive electrode material has both excellent cycle stability and rate performance.

[0041] The preparation method of the positive electrode material provided in the present application divides the sintering process into N (N≥3) step temperature rising sections and a constant temperature section. In each step temperature rising section, there are sub-stages with n different heating rates, the heating rate of the nth sub-stage is greater than the heating rate of the first sub-stage, and the heating rate of the nth sub-stage is a non-negative value. Since the heating rate of the last sub-stage is greater than the heating rate of the first sub-stage: in the nth sub-stage, the particle growth rate increases rapidly, and the internal defects of the particles increase significantly; in the first sub-stage, the particle growth rate tends to be stable, so that the internal defects of the particles are less and the particle size is more uniform. In the constant temperature section, some defects inside the particles can be slowly repaired as the single crystal grows, and the intergranular stress inside the particles is gradually released, which can improve the insufficient strength of the particles and the easy cracking caused by excessive internal stress of the particles. The positive electrode material prepared by the present application can improve the particle strength of the positive electrode material, reduce the polarization phenomenon of the positive electrode material, and make the positive electrode material have both excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0043] Figure 1 A schematic diagram of the process for preparing the positive electrode material provided in an embodiment of the present application.

[0044] Figure 2 This is a schematic diagram of the peak separation of the (104) characteristic peak of the positive electrode material provided in Example 1 of the present application.

[0045] Figure 3 This is a temperature curve diagram of the primary sintering in the method for preparing the positive electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0046] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0047] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0048] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0049] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.

[0050] The present application provides a positive electrode material, the positive electrode material is a nickel-cobalt-lithium oxide composite oxide;

[0051] The positive electrode material is measured by XRD to obtain a characteristic peak I(104) corresponding to the (104) crystal plane of the positive electrode material. The characteristic peak I(104) is separated into two diffraction peaks, and the separation degree α of the two diffraction peaks satisfies: 0.7≤α≤2.0.

[0052] The positive electrode material provided in the present application controls the two diffraction peaks obtained by the peak separation of the characteristic peak I(104) corresponding to the (104) crystal plane of the positive electrode material, and the separation degree of the two diffraction peaks is in the range of 0.7 to 2.0. On the one hand, it can ensure that the particle size of the positive electrode material is within an appropriate range, and reduce the deterioration of capacity and rate performance caused by the substantial increase in the lithium ion diffusion distance caused by excessively large particles. In addition, the appropriate particle size can improve the structural strength of the particles, improve the cracking / powdering of the particles under high rolling pressure and high voltage windows, and improve the cycle performance of the positive electrode material. On the other hand, the separation degree is in the range of 0.7 to 2.0, which can ensure that the degree of internal defects of the positive electrode material particles is within an appropriate range, and improve the Li + The phenomenon of low diffusion rate and increased internal defects of the particles can enrich the diffusion path of lithium ions, reduce the time required for lithium ion diffusion, make the degree of lithium deintercalation inside and on the surface of the positive electrode material particles tend to be consistent, and improve the polarization phenomenon between the surface and inside of the particles. Therefore, the positive electrode material provided by the present application can improve the particle strength of the positive electrode material, reduce the polarization phenomenon of the positive electrode material, and make the positive electrode material have both better cycle stability and rate performance.

[0053] In some embodiments, the characteristic peak I (104) is a non-left-right symmetrical structure, and the two diffraction peaks after peak separation are left-right symmetrical structures, that is, the diffraction peak curve is normally distributed.

[0054] In some embodiments, the value range of α can be 0.7, 0.75, 0.8, 0.82, 0.85, 0.88, 0.90, 0.95, 0.98, 1.0, 1.05, 1.08, 1.1, 1.15, 1.2, 1.4, 1.58, 1.6, 1.8 or 2.0, etc., and of course, it can also be other values ​​within the above range. When the separation degree α is less than 0.7, the single crystal particles of the positive electrode material are small, the particle strength is insufficient, and it is easy to crack and pulverize during the cycle process, which affects the cycle life of the material; and when the particle size is small, the tap density of the positive electrode material decreases, the internal defects of the positive electrode material particles are insufficient, and the lithium ion diffusion path is single, resulting in an increase in the polarization phenomenon between the surface and the interior of the particle, and a decrease in the cycle life. When the separation degree α is greater than or equal to 0.7 and less than or equal to 2.0, the particle size is larger, the tap density of the positive electrode material increases, and the particle strength is higher; at the same time, the internal defects of the particle material increase, the Li+ diffusion path increases, and the internal and surface polarization of the material particles weakens during the charge and discharge process; the cycle and rate performance are both better. When the separation degree α is greater than 2.0, the particle size is too large, resulting in an increase in the lithium ion diffusion path, increased polarization, and deterioration of the capacity and rate performance. Therefore, when the separation degree α is controlled within the above range, the positive electrode material can have both a larger single crystal particle size and more internal structural defects, thereby having better cycle performance and capacity rate performance.

[0055] In some embodiments, the positive electrode material has the general chemical formula Li a Ni x Co y M1 z M2 k O2, wherein M1 is selected from Mn and / or Al, and M2 includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La and Dy; wherein 0.9<a≤1.1, 0.33≤x≤1, 0≤y≤0.33, 0<z<0.33, 0≤k<0.1, and x+y+z+k=1.

[0056] Specifically, the value range of a can be 0.9, 0.95, 0.98, 1.0, 1.01, 1.02, 1.03, 1.05, 1.1, etc., the value range of x can be 0.33, 0.45, 0.5, 0.55, 0.6, 0.7, 0.8, 0.9 or 1, etc., the value range of y can be 0, 0.02, 0.05, 0.07, 0.08, 0.1, 0.15, 0.2, 0.25, 0.28, 0.30 or 0.33, etc., the value range of z can be 0.01, 0.06, 0.1, 0.15, 0.2, 0.25 or 0.3, etc. The value range of k can be 0, 0.001, 0.005, 0.01, 0.02, 0.05 or 0.099, etc.

[0057] It should be noted that the content of each element in the positive electrode material can be measured by a known instrument for qualitative analysis and / or quantitative analysis of each element, such as ICP and ICP-MS.

[0058] In some embodiments, the SEM morphology of the positive electrode material is measured by a scanning electron microscope. The positive electrode material is a single crystal positive electrode material. The single crystal positive electrode material has a more stable structure, a more uniform distribution of bulk components, and better particle strength than a polycrystalline positive electrode material. It can provide lithium-ion batteries with better cycle stability and safety, and can also significantly reduce particle cracking during the pole piece pressing process, thereby increasing the pole piece compaction density and volume energy density.

[0059] In some embodiments, M2 includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La and Dy. These doping elements can change the lattice constant of the positive electrode material or the valence state of the elements in the material, reduce cation mixing, improve the electronic conductivity and ionic conductivity of the material, improve the stability of the material structure, inhibit structural collapse, and thus improve the performance of the positive electrode material.

[0060] In some embodiments, the positive electrode material satisfies the following relationship: 1≤T-(1.04α-0.25α 2 +0.004*D 50 2 -0.02*D 50 )≤1.5; where T represents the tap density of the positive electrode material, in g / cm 3 ;D 50 It represents the median particle size of the positive electrode material in μm.

[0061] In the above scheme, by controlling the tap density T and particle size D of the positive electrode material 50 When the relationship among the three is within the above range, the energy density, particle strength and defect degree of the material can be balanced, so that the positive electrode material has both better cycle stability and rate performance.

[0062] Conventional cathode materials are generally prepared by controlling the tap density T, particle size D 50 The relationship between the cycle stability and rate performance is used to balance the cycle stability and rate performance, but the effect of the separation degree α on the electrochemical performance of the positive electrode material is not considered, which has a major defect. In order to obtain a higher energy density, a higher tap density and particle size D are selected. 50 The positive electrode material has low rate performance. In order to obtain higher rate performance, a lower tap density and D 50 The positive electrode material results in low energy density and cycle stability of the positive electrode material, making it difficult to balance the electrical performance indicators well.

[0063] This application controls the tap density T and particle size D of the positive electrode material 50 When the relationship between the three is within the above range, in order to obtain a higher energy density, a higher tap density and a lower D 50 The positive electrode material is controlled to increase the value of separation degree α appropriately (not higher than 2.0), so that the three equations still satisfy the above equation. At this time, the number of particle defects inside the positive electrode material is large, and Li + The increase in diffusion paths enables the positive electrode material to have both higher energy density and better rate performance. In order to obtain higher rate performance, a lower tap density and a larger D 50 The positive electrode material is made of a material having a certain thickness, and the value of α is controlled to be appropriately reduced (not less than 0.7), so that the three equations still satisfy the above equation. At this time, the particle size of the positive electrode material is reduced but the structural strength of the particles is not low, which can reduce the cracking / powdering phenomenon of the particles of the positive electrode material under high rolling pressure and high voltage window, so that the positive electrode material can have both better cycle stability and rate performance.

[0064] In some embodiments, the tap density of the positive electrode material is T g / cm 3, 1.7≤T≤2.5; specifically, it can be 1.7g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 or 2.5g / cm 3 The tap density of the positive electrode material is one of the indicators of the material's energy density. If the tap density of the positive electrode material is too large, the positive electrode sheet is too dense, which is not conducive to the electrolyte infiltration of the positive electrode sheet, and lithium ions are not easily embedded, resulting in a decrease in the battery's rate performance. If the tap density of the positive electrode material is too low, the material's energy density will decrease. The present application controls the tap density within the above range, so that the positive electrode material can have both high energy density, particle strength and excellent rate performance.

[0065] In some embodiments, the median particle size D of the positive electrode material is 50 μm, 3≤D 50 ≤16. , specifically, it can be 3μm, 4μm, 5μm, 8μm, 10μm, 12μm, 15μm or 16μm, etc., which are not limited here. When the D50 value is small, the corresponding positive electrode material particle size is small, the tap density is low, and the specific surface area is large, resulting in serious side reactions between the particle surface and the electrolyte, and the safety and cycle life are greatly reduced; when the D50 value is large, the corresponding positive electrode material particle size is large, the internal stress of the particle increases, and the lithium ion concentration polarization is intensified, resulting in a decrease in the capacity and rate performance of the positive electrode material. When the particle size D50 is controlled within the above range, the positive electrode material has better compaction density, gram capacity and cycle life.

[0066] In some embodiments, the positive electrode material satisfies the following relationship: 125≤C-(100*n Ni -D 50 *α 2 )≤135; where C represents the gram capacity of the positive electrode material, in mAh / g; D 50 Indicates the median particle size of the positive electrode material, in μm; n Ni It represents the molar ratio of Ni element in all metal elements except Li element in the positive electrode material. Controlling the positive electrode material to satisfy the above relationship can improve the particle strength of the positive electrode material, reduce the polarization phenomenon of the positive electrode material, and make the positive electrode material have both better cycle stability and rate performance.

[0067] In some embodiments, the gram capacity of the positive electrode material is C mAh / g, 140≤C≤230; specifically, it can be 140, 160, 170, 180, 190, 200, 220 or 230, etc., and of course, it can also be other values ​​within the above range, which are not limited here. It should be noted that the gram capacity of the positive electrode material is the discharge capacity of the full battery made of the positive electrode material under 0.33C / 0.33C@3.0-4.3V, 25°C. By controlling the gram capacity within the above range, the positive electrode material can have both better energy density and cycle life. Preferably, 170≤C≤220.

[0068] In some embodiments, the molar ratio of Ni element in all metal elements except Li element in the positive electrode material is n Ni , 0.33≤n Ni ≤1.n Ni Specifically, it can be 0.33, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.8, 0.9 or 1, etc. Of course, other values ​​within the above range are also possible, and are not limited here. Controlling n Ni Within the above range, the gram capacity of the positive electrode material can be guaranteed to be within an appropriate range, thereby increasing the energy density of the lithium-ion battery; at the same time, the n Ni Reduce the bring n Co Increase can control production costs and improve the cost performance of unit energy density. Ni This can make the positive electrode material have better cost performance, energy density and cycle life.

[0069] In some embodiments, the positive electrode material satisfies the following relationship: 1800≤L-(2245α-5000*n Ni +100*D 50 )≤2400; where L represents the cycle life of the positive electrode material; D 50 Indicates the median particle size of the positive electrode material, in μm; n Ni It represents the molar ratio of Ni element in all metal elements except Li element in the positive electrode material. Controlling the positive electrode material to satisfy the above relationship can improve the particle strength of the positive electrode material, reduce the polarization phenomenon of the positive electrode material, and make the positive electrode material have better cycle stability and rate performance.

[0070] In some embodiments, the cycle life of the positive electrode material is L cycles, 300≤L≤6000; specifically, it can be 300, 500, 800, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500 or 6000, etc. Of course, it can also be other values ​​within the above range, which are not limited here. It should be noted that the full battery made of the positive electrode material is charged and discharged under 1C / 1C@3.0-4.3V, 25°C conditions until the capacity retention rate reaches 80%, and the number of cycles is recorded as the cycle life L. When L is controlled within the above range, the positive electrode material has a better energy density and cycle life. L is the measured value of the corresponding lithium-ion battery cycle life, which is affected by n Ni The influence is large and is closely related to the particle size D50 and the separation degree α. When the particle size D50 and the separation degree α fluctuate, the L value deviates from the above range, and the cycle life of the battery is too low, affecting practicality. In order to have both the energy density and practicality of the positive electrode material, preferably, 1000≤L≤4000.

[0071] In a second aspect, the present invention provides a method for preparing a positive electrode material, such as Figure 1 As shown, the following steps are included:

[0072] Step S10, subjecting the mixture containing the cathode material precursor and the lithium source to a primary sintering treatment, and crushing the primary sintering product to obtain the cathode material; wherein the primary sintering treatment includes N step temperature rising sections and constant temperature sections performed in sequence, N≥3;

[0073] Each step heating section includes n sub-stages with different heating rates, n≥2, the heating rate of the nth sub-stage is greater than the heating rate of the first sub-stage, and the heating rate of the nth sub-stage is a non-negative value.

[0074] In the above technical scheme, the sintering process is divided into N (N≥3) step heating sections and constant temperature sections. In each step heating section, there are sub-stages with n different heating rates, the heating rate of the nth sub-stage is greater than the heating rate of the first sub-stage, and the heating rate of the nth sub-stage is non-negative. Since the heating rate of the last sub-stage is greater than the heating rate of the first sub-stage, in the nth sub-stage, the particle growth rate increases rapidly and the internal defects of the particles increase significantly; in the first sub-stage, the particle growth rate tends to be stable, so that the internal defects of the particles are less and the particle size is more uniform. In the constant temperature section, some defects inside the particles can be slowly repaired as the single crystal grows, and the intergranular stress inside the particles is gradually released, which can improve the insufficient strength of the particles and easy cracking caused by excessive internal stress of the particles. The positive electrode material prepared in this application can improve the particle strength of the positive electrode material, reduce the polarization phenomenon of the positive electrode material, and make the positive electrode material have both excellent cycle stability and rate performance.

[0075] The preparation method of the present application is described in detail below with reference to the examples:

[0076] Before step S10, the method further includes:

[0077] S10, subjecting the mixture including the cathode material precursor and the lithium source to a primary sintering treatment, and crushing the primary sintering product to obtain the cathode material.

[0078] In some embodiments, the chemical formula of the cathode material precursor is Ni a1 Co b1 M1 c1 O d , wherein 0.33≤a1≤1, 0≤b1≤0.33, 0≤c1<0.33, 4 / 3≤d≤3 / 2, and a1+b1+c1=1, and M1 is selected from Mn and / or Al.

[0079] In some embodiments, the chemical formula of the cathode material precursor is Ni a2 Co b2 M1 c2 (OH)2, wherein 0.33≤a2≤1, 0≤b2≤0.33, 0≤c2<0.33, and a2+b2+c2=1, and M1 is selected from Mn and / or Al.

[0080] In some embodiments, the median particle size of the positive electrode material precursor is 3 μm to 18 μm, specifically 3 μm, 4 μm, 5 μm, 7 μm, 8 μm, 10 μm, 12 μm, 15 μm or 18 μm, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0081] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, lithium acetate, lithium sulfate, and lithium oxalate.

[0082] In some embodiments, the amount of lithium source and cathode material precursor added satisfies: the ratio of the molar amount of Li to the total molar amount of all metals in the cathode material precursor is (0.9-1.1):1. Specifically, it can be 0.9:1, 0.95:1, 0.98:1, 1:1, 1.02:1, 1.05:1, 1.1:1, etc. Of course, it can also be other values ​​within the above range, which are not limited here. Within this range, it can reduce the degree of Li / Ni cation mixing and reduce the excessive residual lithium on the surface of the sintered product that affects the processing performance and safety performance.

[0083] In some embodiments, the mixture further includes a dopant containing metal M2, and the M2 metal includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La, and Dy. Specifically, it may contain a salt or oxide of metal M2.

[0084] In some embodiments, the amount of dopant added is controlled so that the ratio of the molar amount of M2 to the total molar amount of transition metal in the prepared positive electrode material is (0-0.1):1. Specifically, it can be 0.01:1, 0.02:1, 0.05:1, 0.07:1, 0.08:1, 0.09:1 or 0.1:1, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0085] In some embodiments, the solid phase mixing method can be dry grinding, ball milling, etc., which is not limited here, as long as the components are mixed evenly.

[0086] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, a coating machine, and a VC mixer.

[0087] In some embodiments, the primary sintering process is carried out in an oxygen-containing atmosphere, and the volume content of oxygen in the oxygen-containing atmosphere is ≥ 20%. The volume content of oxygen in the oxygen-containing atmosphere can be 20%, 30%, 40%, 50%, 60%, 70%, 80% or 100%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. In order to fully carry out the reaction, preferably, the volume content of oxygen in the oxygen-containing atmosphere is ≥ 90%.

[0088] In some embodiments, the maximum temperature of the step temperature rising section is 700°C to 1000°C, specifically 700°C, 800°C, 850°C, 900°C, 950°C, 980°C, 1000°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] In some embodiments, the time of the step temperature rise section is 6h to 14h, specifically 6h, 7h, 8h, 9h, 10h, 12h, 14h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] In some embodiments, each step heating section includes n sub-stages with different heating rates, n≥2, the heating rate of the nth sub-stage is greater than the heating rate of the 1st sub-stage, and the heating rate of the nth sub-stage is a non-negative value.

[0091] Of course, a step heating section can also be formed by combining three or more sub-stages with different heating rates. For example, the first heating rate can be 250°C / h, 230°C / h, 200°C / h, etc., and the second heating rate can be 190°C / h, 180°C / h, 150°C / h, etc.

[0092] The inventors have found that the more the number of step-temperature rise sections is, the greater the difference between the temperature rise rate of the first sub-stage and the temperature rise rate of the last sub-stage is, and the separation degree α of the positive electrode material can be better controlled within an appropriate range.

[0093] Understandably, when the heating rate is fast, the growth rate of single crystal particles changes rapidly, the particle size is uneven, and the number of defects in the grains increases significantly; when the heating rate is slow, the single crystal particles tend to grow stably, the particle size is uniform, and the defects inside the grains are slowly repaired as the single crystal grows. In the alternating changes of the heating rate between fast and slow, the stress and number of defects inside the grains can be taken into account, so that the positive electrode material will not be insufficient in particle strength and easy to crack due to excessive internal stress, nor will it cause Li+ due to insufficient internal defects. + The diffusion path is single and polarization is severe.

[0094] In some embodiments, the heating rate of the first sub-stage in each step heating section is less than the heating rate of the nth sub-stage, and the heating rate of the nth sub-stage is a non-negative value.

[0095] In some embodiments, the sintering temperature of the constant temperature section ranges from (1150-500*n Ni )℃~(1150-280*n Ni )℃,n Ni Indicates the molar ratio of Ni element in all metal elements except Li element in the positive electrode material, 0.33≤n Ni ≤1.

[0096] Specifically, the constant temperature section may be a period of time in which the temperature remains constant, or may be composed of a plurality of temperature sections that change back and forth.

[0097] In some embodiments, the constant temperature section includes alternating temperature-lowering subsections and temperature-raising subsections, and the temperature of the temperature-lowering subsection in the constant temperature section is lower than the temperature of the adjacent temperature-raising subsection.

[0098] In some embodiments, the method further comprises: mixing the primary sintering product with a coating agent containing metal M2, and then performing a secondary sintering treatment to obtain a positive electrode material.

[0099] In some embodiments, the mass ratio of the coating agent containing the metal M2 to the primary sintered product is (0-0.1): 1. Specifically, it can be 0:1, 0.002:1, 0.005:1, 0.01:1, 0.03:1, 0.05:1 or 0.1:1, etc., which is not limited here.

[0100] In some embodiments, the coating agent containing metal M2, the M2 metal includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La and Dy. The coating agent containing metal M2 can be a salt or oxide of metal M2. Preferably, the coating agent containing metal M2 includes a Co compound and / or a W compound.

[0101] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 20%.

[0102] In some embodiments, the temperature of the secondary sintering process is 300°C to 900°C. Specifically, it can be 300°C,

[0103] 380°C, 450°C, 550°C, 600°C, 700°C, 750°C, 800°C, 840°C or 900°C, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] In some embodiments, the holding time of the secondary sintering treatment is 6 hours to 24 hours. Specifically, it can be 6 hours, 8 hours,

[0105] 10h, 12h, 15h, 18h or 24h, etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0106] In some embodiments, the crushing method includes at least one of a double roller, a plowshare mixer / crusher, a jet mill, and a mechanical mill.

[0107] In some embodiments, the preparation method further comprises cooling, shaping and screening the product after secondary sintering. The shaping comprises at least one of crushing, grinding, ball milling or gas crushing.

[0108] In some embodiments, the sieving uses a screen with a mesh size of 300 to 400 mesh.

[0109] In a third aspect, the present application provides a battery, the battery comprising the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned preparation method.

[0110] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0111] Example 1

[0112] A method for preparing a positive electrode material comprises the following steps:

[0113] (1) Ni precursor with a D50 of 4.0 μm 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3 and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture.

[0114] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), a step temperature rise section 4 (550°C → 0.5h, 570°C → 0.5h, 700°C), and a step temperature rise section 5 (600°C → 0.5h, 700°C → 0.5h, 800°C). Step temperature rise section 5 (700℃→0.5h, 720℃→0.5h, 850℃), step temperature rise section 6 (850℃→0.5h, 830℃→0.8h, 920℃), step temperature rise section 7 (920℃→1h, 900℃→1h, 970℃), constant temperature section (970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h).

[0115] (3) The sintered material is crushed and sieved to obtain the matrix material.

[0116] (4) The base material is uniformly mixed with Al2O3 and Co(OH)2 in a weight ratio of 1:0.002:0.04, and calcined at 850°C for 8 hours, and then cooled, crushed, sieved, and demagnetized to obtain a positive electrode material.

[0117] Figure 3 This is a temperature curve diagram of the primary sintering in the method for preparing the positive electrode material provided in Example 1 of the present application, such as Figure 3As shown in the figure, the "multi-step" temperature curve schematic diagram includes a step heating section and a constant temperature section. The step heating section includes 7 sub-stages, each of which contains 2 sections with different heating rates; and each step heating section satisfies the setting that the second section heating rate > the first section heating rate, and the first section heating rates of the 1st to 5th step heating sections are all positive. The heating rate of the first sub-stage in the 6th to 7th step heating sections is a negative value, and the heating rate of the second sub-stage is a non-negative value.

[0118] Example 2

[0119] The difference from Example 1 is:

[0120] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), and a step temperature rise section 4. (550℃→0.5h, 570℃→0.5h, 700℃), step heating section 5 (700℃→0.5h, 720℃→0.5h, 850℃), step heating section 6 (850℃→1h, 830℃→0.8h, 920℃), step heating section 7 (920℃→0.7h, 900℃→1h, 970℃), constant temperature section (970℃→8h, 970℃).

[0121] Example 3

[0122] The difference from Example 1 is:

[0123] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.3h, 400°C), a step temperature rise section 3 (400°C → 0.6h, 420°C → 0.4h, 550°C), a step temperature rise section 4 (550°C → 0.5h, 57 0℃→0.4h, 700℃), step temperature rising section 5 (700℃→0.5h, 720℃→0.3h, 850℃), step temperature rising section 6 (850℃→0.5h, 870℃→0.5h, 970℃), constant temperature section (970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h, 950℃→1h, 970℃→1h).

[0124] Example 4

[0125] The difference from Example 1 is:

[0126] (2) the mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), and a step temperature rise section 4 (550°C → 0.5h, 570°C → 0.5h, 700°C). Step heating section 5 (700℃→0.5h, 720℃→0.5h, 850℃), step heating section 6 (850℃→1h, 830℃→0.8h, 920℃), step heating section 7 (920℃→1h, 900℃→1h, 950℃), constant temperature section (950℃→1h, 930℃→1h, 950℃→1h, 930℃→1h, 950℃→1h, 930℃→1h, 950℃→1h, 930℃→1h, 950℃→1h, 950℃→1h, 930℃→1h, 950℃→1h).

[0127] Example 5

[0128] The difference from Example 4 is:

[0129] (1) Ni precursor with a D50 of 10 μm 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3 and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture.

[0130] Example 6

[0131] The difference from Example 4 is:

[0132] (1) Ni precursor with a D50 of 16 μm 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3 and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture.

[0133] Example 7

[0134] The difference from Example 1 is:

[0135] (1) Ni precursor with a D50 of 4.0 μm 0.5 Co 0.2 Mn 0.3 (OH)2, Li2CO3 and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0136] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), a step temperature rise section 4 (550°C → 0.5h, 570°C → 0.5h, 700°C), and a step temperature rise section 5 (600°C → 0.5h, 700°C → 0.5h, 800°C). Step temperature rise section 5 (700℃→0.5h, 720℃→0.5h, 850℃), step temperature rise section 6 (850℃→1h, 830℃→0.8h, 920℃), step temperature rise section 7 (920℃→0.7h, 900℃→1h, 990℃), constant temperature section (990℃→1h, 970℃→1h, 990℃→1h, 970℃→1h, 990℃→1h, 970℃→1h, 990℃→1h, 970℃→1h, 990℃→1h, 970℃→1h, 990℃→1h).

[0137] Example 8

[0138] The difference from Example 1 is:

[0139] (1) Ni precursor with a D50 of 4.0 μm 0.7 Co 0.1 Mn 0.2 (OH)2, LiOH·H2O and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0140] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), a step temperature rise section 4 (550°C → 0.5h, 570°C → 0.5h, 700°C), and a step temperature rise section 5 (600°C → 0.5h, 700°C → 0.5h, 800°C). Step temperature rise section 5 (700℃→0.5h, 720℃→0.5h, 850℃), step temperature rise section 6 (850℃→1h, 830℃→0.8h, 920℃), step temperature rise section 7 (920℃→0.7h, 900℃→1h, 930℃), constant temperature section (930℃→1h, 910℃→1h, 930℃→1h, 910℃→1h, 930℃→1h, 910℃→1h, 930℃→1h, 910℃→1h, 930℃→1h, 910℃→1h, 930℃→1h).

[0141] Example 9

[0142] The difference from Example 1 is:

[0143] (1) Ni precursor with a D50 of 4.0 μm 0.8 Co 0.1 Mn 0.1 (OH)2, LiOH·H2O and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0144] (2) The mixture 1 is sintered once in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), a step temperature rise section 4 (550°C → 0.5h, 570°C → 0.5h, 700°C), a step temperature rise section 5 (600°C → 0.5h, 700°C → 0.5h, 800°C), and a step temperature rise section 6 (700°C → 0.5h, 800°C → 0.5h, 900°C). 5 (700℃→0.5h, 720℃→0.5h, 850℃), step heating section 6 (850℃→1h, 830℃→0.8h, 860℃), step heating section 7 (860℃→0.7h, 840℃→1h, 870℃), constant temperature section (870℃→1h, 890℃→1h, 870℃→1h, 890℃→1h, 870℃→1h, 890℃→1h, 870℃→1h, 890℃→1h, 870℃→1h, 890℃→1h, 870℃→1h, 890℃→1h).

[0145] Example 10

[0146] The difference from Example 1 is:

[0147] (1) Ni precursor with a D50 of 4.0 μm 0.9 Co 0.05 Mn 0.05 (OH)2, LiOH·H2O and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0148] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), a step temperature rise section 4 ( The heating stage was as follows: 550℃→0.5h, 570℃→0.5h, 700℃), step heating stage 5 (700℃→0.5h, 720℃→0.5h, 850℃), constant temperature stage (850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h).

[0149] Embodiment 11

[0150] The difference from Example 1 is:

[0151] (1) Ni precursor with a D50 of 4.0 μm 0.9 Co 0.05 Mn 0.05 (OH)2, LiOH·H2O and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0152] (2) The mixture 1 is sintered in a dry air atmosphere according to the following temperature curve, including a step temperature rise section 1 (0°C → 0.2h, 50°C → 0.5h, 250°C), a step temperature rise section 2 (250°C → 0.5h, 270°C → 0.5h, 400°C), a step temperature rise section 3 (400°C → 0.5h, 420°C → 0.5h, 550°C), a step temperature rise section 4 ( The heating stage was as follows: 550℃→0.5h, 570℃→0.5h, 700℃), step heating stage 5 (700℃→0.5h, 720℃→0.5h, 830℃), constant temperature stage (830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h, 830℃→1h, 850℃→1h).

[0153] Comparative Example 1

[0154] The difference from Example 1 is:

[0155] (2) The mixture is sintered in a dry air atmosphere according to a temperature curve of uniform heating rate + constant temperature section: 0h, 0°C → 8h, 950°C → 8h, 950°C.

[0156] Comparative Example 2

[0157] The difference from Example 1 is:

[0158] (2) The mixture is sintered in a dry air atmosphere according to a temperature curve of uniform heating rate + constant temperature section: 0h, 0°C → 2h, 960°C → 8h, 960°C.

[0159] Comparative Example 3

[0160] The difference from Example 1 is:

[0161] (2) The mixture is sintered in a dry air atmosphere according to a temperature curve of uniform heating rate + constant temperature section: 0h, 0°C → 4h, 850°C → 3h, 850°C → 1h, 950°C → 8h, 950°C.

[0162] Comparative Example 4

[0163] The difference from Example 1 is:

[0164] (1) Ni precursor with a D50 of 10 μm 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3 and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0165] (2) The mixture is sintered in a dry air atmosphere according to a temperature curve of uniform heating rate + constant temperature section: 0h, 0°C → 8h, 950°C → 8h, 950°C.

[0166] Comparative Example 5

[0167] The difference from Example 1 is:

[0168] (1) Ni precursor with a D50 of 16 μm 0.6 Co 0.1 Mn 0.3 (OH)2, Li2CO3 and ZrO2 are uniformly mixed in a ratio of 1:1.05:0.25% to obtain a mixture;

[0169] (2) The mixture is sintered in a dry air atmosphere according to a temperature curve of uniform heating rate + constant temperature section: 0h, 0°C → 8h, 950°C → 8h, 950°C.

[0170] Preparation of positive electrode

[0171] The positive electrode material prepared in the embodiment or comparative example, the binder polyvinylidene fluoride (PVDF), the conductive agent acetylene black and the conductive liquid are dissolved in the solvent N-methylpyrrolidone (NMP) at a weight ratio of 96:2:1.5:0.5, and the mixture is fully stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode current collector with the primer, and then dried, cold pressed and cut to obtain a positive electrode sheet with a surface density of 350 g / m 2 , compacted density 3.5g / cm 3 .

[0172] Negative electrode sheet preparation

[0173] The active material graphite, binder SBR, and conductive agent acetylene black were dissolved in deionized water in a weight ratio of 96:2:2, and evenly mixed to prepare a negative electrode slurry. The slurry was coated on a copper foil, dried, and cold-pressed to obtain a negative electrode sheet. The surface density of the negative electrode sheet was 210 g / m 2 , compacted density 1.6g / cm 3 .

[0174] Diaphragm

[0175] The diaphragm is a PE diaphragm with PVDF and alumina coating on the surface to improve adhesion and heat resistance.

[0176] Electrolyte

[0177] Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of lithium salt is 1.1 mol / L, and the electrolyte also contains 2% by weight of vinylene carbonate and 1% by weight of polysulfone.

[0178] Preparation of batteries

[0179] The ratio of the negative electrode capacity to the positive electrode capacity of the battery (N / P) is controlled to be 1.1, and the injection amount of the electrolyte is 3.2g / Ah; the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes the processes of static, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a lithium-ion battery product.

[0180] Performance Testing

[0181] 1. Battery capacity test system: At 25°C, charge to 4.3V in CCCV mode (charging current 0.33C, constant voltage cut-off current 0.01C), let stand for 10 minutes, discharge to 3.0V in CC mode (discharge current 0.33C), and calculate the discharge capacity C mAh / g based on the discharge capacity;

[0182] 2. Battery rate test system: After the battery capacity test is completed, continue to test according to the following system: at 25℃, stand for 10 minutes, charge to 4.3V in CCCV mode (charging current 0.33C, constant voltage cut-off current 0.01C), stand for 10 minutes, discharge to 3.0V in CC mode (discharge current 2.0C), the discharge capacity is recorded as C R mAh / g, the rate performance R=C is obtained by the following calculation R / C*100%.

[0183] 3. Cycle test system: Take the formed and capacity-divided battery, charge it to 4.3V in CCCV mode (charging current 1.0C, constant voltage cut-off current 0.1C) at 25℃, let it stand for 10min, discharge it to 3.0V in CC mode (discharge current 1.0C) to get the initial gram capacity C1 mAh / g, let it stand for 10min; then repeat CCCV mode charging and CC mode discharging until the discharge gram capacity is less than 0.8*C1 mAh / g; record the cumulative number of discharges as the cycle life.

[0184] 4. Test method for tap density of positive electrode materials

[0185] Adopt GB / T5162-1985 metal powder-determination of tap density.

[0186] 5. Test method for particle size of positive electrode material:

[0187] The particle size test method refers to GB / T 19077-2016. It can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0188] 6. Test method of nNi of positive electrode material:

[0189] The test method of nNi refers to GB / T 24194-2009. It can be conveniently measured by inductively coupled plasma optical emission spectrometer (ICP-OES), such as Agilent 5110 ICP-OES.

[0190] 7. XRD test of positive electrode material:

[0191] The positive electrode material is measured by XRD rays to obtain a characteristic peak I(104) corresponding to the (104) crystal plane of the positive electrode material. The characteristic peak I(104) is separated into two diffraction peaks, namely (104)-Kα1 and (104)-Kα2. The peak positions of the (104)-Kα1 and (104)-Kα2 diffraction peaks are P1 and P2, respectively, and the half-widths are FWHM1 and FWHM2, respectively. The separation degree α can be calculated as 2*(P2-P1) / (FWHM1+FWHM2).

[0192] In this application, T-(1.04α-0.25α 2 +0.004*D 50 2 -0.02*D 50 ) is recorded as X, C-(100*n Ni -D 50 *α 2) is recorded as Y, L-(2245α-5000*n Ni +100*D 50 ) is denoted as Z.

[0193] Table 1 Performance of positive electrode materials and battery performance parameters

[0194]

[0195]

[0196] As shown in Table 1, Examples 1 to 4 were prepared using the same raw materials, and the median particle size D of the obtained positive electrode materials was 50 The results are similar, but due to the difference in temperature curves, the single crystal particle size and the number of internal defects are different. Compared with Example 1, the constant temperature section temperature of Example 2 lacks fluctuations, so its particle size is larger than that of Example 1, and the number of internal defects in the crystal of the positive electrode material of Example 2 is slightly reduced, and the α value is slightly increased. Compared with Example 1, the heating rate of Example 3 is significantly increased, the number of internal defects in the crystal is greatly increased, the number of lithium ion active sites is increased, and the α value is improved. Compared with Example 1, the temperature of the constant temperature section of Example 4 is lowered, the single crystal particle size is reduced compared with Example 1, and α is also reduced accordingly.

[0197] According to the test data of Examples 1 to 4, as α increases, the tap density T of the positive electrode material increases, the gram capacity C decreases, and the cycle life L increases. The tap density T, gram capacity C, and cycle life L of the positive electrode material all show a strong correlation with α. Therefore, controlling the separation degree α within the range of 0.7 to 2.0 can improve the particle strength of the positive electrode material and reduce the polarization phenomenon of the positive electrode material, so that the positive electrode material has both better cycle stability and rate performance.

[0198] Examples 4 to 6 are sintered using the same temperature curve, and the characteristic diffraction peak separation α of the (104) crystal plane of the obtained positive electrode materials is close, and the single crystal particle size and the number of internal defects of the crystal are similar. However, due to the difference in the particle size of the positive electrode precursor, the median particle size of the positive electrode material is quite different. According to the test data of Examples 4 to 6, when the separation α is in the range of 0.7 to 2.0, as the particle size D of the positive electrode material increases, the particle size of the positive electrode material increases. 50 Increases, the tap density T increases, the gram capacity C decreases, and the cycle life L increases.

[0199] Example 1, Example 7 to Example 10 adopt similar temperature curves for sintering, and the characteristic diffraction peak separation α, median particle size D50, and tap density TD of the (104) crystal plane of the positive electrode material are relatively close, and the single crystal particle size and the number of internal defects of the crystal are comparable. However, due to the difference in the composition of the positive electrode material precursor, there are obvious differences in their gram capacity C and cycle life L. According to the test data of Example 1 and Example 7 to Example 10, when the separation α is in the range of 0.7 to 2.0, with n Ni As the nickel content increases, the gram capacity C of the positive electrode material also increases. The lithium-nickel mixing caused by the increase in nickel content increases, the side reaction between the positive electrode material and the electrolyte intensifies, and the cycle life also decreases.

[0200] Compared with Example 1, Comparative Examples 1, Comparative Examples 2 and Comparative Examples 3, and compared with Example 1, Comparative Examples 4 and Comparative Examples 5 and Example 6, all adopted a "multi-step" temperature curve that is not described in the present invention for sintering, and the number of internal defects in the crystals is insufficient. Although the median particle size D50 of the obtained positive electrode material is close to that of the corresponding embodiment, the characteristic diffraction peak separation α corresponding to the (104) crystal plane of the positive electrode material is out of the scope of the present application, and it is difficult for the positive electrode material to have both excellent cycle stability and rate performance, and the corresponding X, Y, and Z values ​​fluctuate greatly.

[0201] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is a nickel-cobalt-lithium oxide composite oxide; The positive electrode material is measured by XRD to obtain a characteristic peak I(104) corresponding to the (104) crystal plane of the positive electrode material. The characteristic peak I(104) is separated to obtain two diffraction peaks, namely (104)-Kα1 and (104)-Kα2. The peak positions of the (104)-Kα1 and (104)-Kα2 diffraction peaks are P1 and P2, respectively. The half-peak widths of the (104)-Kα1 and (104)-Kα2 diffraction peaks are FWHM1 and FWHM2, respectively. The separation degree of the two diffraction peaks is calculated to be α=2*(P2-P1) / (FWHM1+FWHM2), and 0.7≤α≤2.

0.

2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies the following relationship: 1≤T-(1.04α-0.25α 2 +0.004*D 50 2 -0.02*D 50 )≤1.5; wherein T represents the tap density of the positive electrode material, in g / cm 3 ;D 50 represents the median particle size of the positive electrode material, in μm.

3. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material satisfies the following relationship: 125≤C-(100*n Ni -D 50 *α 2 )≤135; wherein C represents the gram capacity of the positive electrode material, in units of mAh / g; D 50 represents the median particle size of the positive electrode material, in μm; n Ni It represents the molar proportion of Ni element in all metal elements except Li element in the positive electrode material.

4. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material satisfies the following relationship: 1800≤L-(2245α-5000*n Ni +100*D 50 )≤2400; where L represents the cycle life of the positive electrode material; D 50 Indicates the median particle size of the positive electrode material, in μm; n Ni It represents the molar ratio of Ni element in all metal elements except Li element in the positive electrode material.

5. The positive electrode material according to claim 1 or 2, characterized in that: It meets at least one of the following characteristics: (1) The tap density of the positive electrode material is T g / cm 3 , 1.7≤T≤2.5; (2) The median particle size D of the positive electrode material 50 μm, 3≤D 50 ≤16; (3) The gram capacity of the positive electrode material is C mAh / g, 140≤C≤230; (4) In the positive electrode material, 0.33≤n Ni ≤1; (5) The cycle life of the positive electrode material is L cycles, 300≤L≤6000.

6. The positive electrode material according to claim 1 or 2, characterized in that: The positive electrode material is a single crystal positive electrode material.

7. The positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the positive electrode material is Li a Ni x Co y M1 z M2 k O2, wherein M1 is selected from Mn and / or Al, and M2 includes at least one of Ni, Co, Mn, Na, K, Mg, Ca, Sr, Al, Ti, Y, Zr, W, Nb, Ce, La and Dy; wherein 0.9<a≤1.1, 0.33≤x≤1, 0≤y≤0.33, 0<z<0.33, 0≤k<0.1, and x+y+z+k=1.

8. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for synthesizing positive electrode material of nickel-cobalt-manganese polybasic lithium ion battery by microwave sintering

    CN102157725A

  • Powderous lithium cobalt-based oxide compound for rechargeable lithium ion batteries and a method for making thereof

    US20210028454A1